Perluasan Segmen Pasar UKM Pembudidaya Ikan Berbasis E-Commerce Menggunakan Aplikasi Fishket di Era Revolusi 4.0 - Inka Kris Dwi Cahyono; Amelia Puji Astuti; Nur Hikma Eka Sari; Regina Suci Fitria; Yunita Fitriyani; Tanbiyaskur Tanbiyaskur (Seminar Nasional Lahan Suboptimal, 2020)
Cahyono IKD, Astuti AP, Sari NHE, Fitria RS, Fitriyani Y, Tanbiyaskur T. 2020. Expansion of fish cultivator-based UKM market segments e-commerce using fishket application in the revolutionary era 4.0. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimalke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Fishery marketing is of particular concern in aquaculture business where the inability of fish cultivators to sell fish produced at high prices is still the main problem to increase income, this is due to the cartel practice where middlemen create and determine low purchase prices from fish cultivators and on the other hand, middlemen design a high selling price to consumers. To overcome this, digital marketing was held, the Fishket application was a solution in marketing and selling crops, where this application can be accessed directly via a Smartphone. This application aims to market online aquaculture products, namely seeds, consumption fish, broodstock and various kinds of ornamental fish. This application is designed using hardware and software where in this application several features have been provided that can make it easier for users to buy the fish they want with a very easy payment method, you can use via transfer or direct payment on the spot (delivery order). This application provides features that facilitate the buying and selling process, such as product image features, product prices, product information and payment methods. The application of the application can be accessed anywhere with coverage throughout South Sumatra. So, with the Fishket application, farmers can determine the selling price of fish without a third party. This application is expected to increase sales and income of farmers.